HOMA-IR Assessment for Impaired Glucose Tolerance, Impaired Fasting Glucose and Insulin Resistance Diagnosis - Severeyn, Erika (Springer Nature, 2019)
Impaired glucose tolerance (IGT), impaired fasting glucose (IFG) and insulin resistance (IR) are prediabetic conditions diagnosed by glucose and insulin values measured by oral glucose tolerance test (OGTT). In the OGTT, insulin and glucose levels are measured in five different blood samples: a sample in fasting (minute 0) and four others after oral intake of 75 gr of glucose, at intervals of 30 min (minute 30, 60, 90, and 120). The values of glucose at 0 and 120 min from OGTT are used for the diagnosis of IFG and IGT, respectively. The HOMA-IR is the most used method of determining IR in large populationbased studies; it is mathematically derived from fasting glucose and insulin measurements from OGTT. One of the limitations of HOMA-IR is the difficulty of predicting IR in populations with IGT. The aim of this study is to evaluate the capability of a HOMA-IR and modified version of HOMA-IR (HOMA-IR calculated from glucose and insulin of 30, 60, 90 and 120 min of OGTT) to diagnose IGT, IR, and IFG. Receiver operating characteristic (ROC) curves and area under the ROC curve (AUC) were performed to assess the predictive capacity of HOMA-IR and modified versions. The present study demonstrated that modified versions of HOMA-IR calculated using glucose and insulin from 60 and 90 min of OGTT are alternative indexes (AUC < 0.70) for IGT, IFG and IR detection.